Gravitation modulation impact on MHD free convection flow of micropolar fluid (Journal of Naval Architecture and Marine Engineering, 2020)
In this paper, a theoretical study is carried out on unsteady three dimensional, laminar, free convective flow of micropolar fluid with Hall effect, Joule heating and heat sink under gravitation modulation. A uniform transverse magnetic field is applied normal to the plate along the fluid region. The magnetic Reynolds number is considered to be small due to incomparability of applied and induced magnetic field, as such the influence of induced magnetic field can be neglected. The multi parameter perturbation technique is used to solve the governed dimensionless equations. The fluid velocity profile, temperature profile and the concentration profiles are discussed with the aid of graphs and tables. The coefficient of skin friction and couple stresses are numerically computed in addition to Nusselt number and Sherwood number. The result reveals that the linear velocity increases due to escalation in gravitation modulation parameter values but for intensification in values of gravitation modulation parameter, a reverse effect is observed for the rotational velocity. A comparative analysis shows that the skin friction coefficient is less in micropolar fluid than the corresponding Newtonian fluids.